Effect of Cocoa Roasting on Chocolate Polyphenols Evolution - Alessandro La Mantia; Federica Ianni; Aurélie Schoubben; Marco Cespi; Klemen Lisjak; Davide Guarnaccia; Roccaldo Sardella; Paolo Blasi (MDPI AG, 2023)
Cocoa and chocolate antioxidants might contribute to human health through, for instance, blood flow improvement or blood pressure and glycemia reduction, as well as cognitive function improvement. Unfortunately, polyphenol content is reduced during cocoa fermentation, drying, roasting and all the other phases involved in the chocolate production. Here, we investigated the evolution of the polyphenol content during all the different steps of chocolate production, with a special emphasis on roasting (3 different roasting cycles with 80, 100, and 130 °C as maximum temperature). Samples were followed throughout all processes by evaluating the total polyphenols content, the antioxidant power, the epicatechin content, and epicatechin mean degree of polymerization (phloroglucinol adducts method). Results showed a similar trend for total polyphenol content and antioxidant power with an unexpected bell-shaped curve: an increase followed by a decrease for the three different roasting temperatures. At the intermediate temperature (100 °C), the higher polyphenol content was found just after roasting. The epicatechin content had a trend similar to that of total polyphenol content but, interestingly, the mean degree of polymerization data had the opposite behavior with some deviation in the case of the highest temperature, probably due to epicatechin degradation. It seems likely that roasting can free epicatechin from oligomers, as a consequence of oligomers remodeling.